Analisis Putusan Pengadilan Tentang Penegakan Hukum Terhadap Pelaku Orang Biasa Yang Melanggar Norma Hukum Kedokteran: (Studi Putusan Nomor 195/Pid.Sus/2021/PN Kpg) - Yuni Farida Duka; Jimmy Pello; Heryanto Amalo (Desentralisasi : Jurnal Hukum, Kebijakan Publik, dan Pemerintahan, 2024)
This study aims to find out and analyze the Court Decision on Law Enforcement Against Ordinary People Who Violate Medical Legal Norms based on the Study of Decision Number 195/Pid.Sus/2021/PN Kpg. This research was carried out using a normative juridical method with the technique of collecting legal materials, library research, then analyzed and compiled systematically. The results of the study show that the Defendant's Actions can be categorized as medical malpractice because they meet four key elements, namely liability, violation, causality, and loss. Given that the perpetrator is an ordinary person and not a medical professional, Article 360 of the Criminal Code is most appropriate to ensnare the perpetrator who is an ordinary person in the case of injury or health disorder because the relevance of Article 360 of the Criminal Code explicitly regulates negligence that causes injuries or health problems.